Phsyiologys Response Two Genotypes of Soybean on Giving α- Tocopherol in Saline Lands - putri tya sumantri; Nini Rahmawati; Mariati Mariati (Jurnal Agroekoteknologi, 2018)
The aim of the research to find out influence of α-tocopherol concentration on physiological of two soybean genotypes. The research was conducted at Desa Paluh Merbau, Percut Sei Tuan, Deli Serdang ± 1.5 m above sea level.  The leaf analysis conducted at Tissue Culture Laboratory of Faculty of Agriculture, University of Sumatera Utara from May to July 2017. The design of the reset was  range by Randomized Block Design with two factors. The first factor was the soybean genotype ie; Grobogan x Anjasmoro and GroboganI x Grobogan and the second was the concentration of α - tocopherol ie; 0, 250, 500 and 750 ppm. The result of research showed that soybean genotypes, the concentration of a-tocopherol and combination between soybean genotypes with concentration  a-tocopherol has no significant effect on all parameters. Nevertheless it appeared that soybean genotypes (GroboganI x Grobogan) produced sod and pod higher than other treatments. The concentration of a-tocopherol 500 ppm produced H2O2, which more less than other treatments. The combination of genotypes (GroboganI x Grobogan) with concentration a-tocopherol 500 ppm produced SOD was higher than other treatments . Keywords :α - tocopherol, saline, soybean genotype